PENGGUNAAAN MODEL SPRINGATE UNTUK MEMPREDIKSI POTENSI KEBANGKRUTAN PERUSAHAAN (Studi Pada Perusahaan Sektor Food and Beverages yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2011 - 2013) - Denhas, Yusuf (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study tries to measure the accuracy level of Springate model in predicting the bankruptcy of companies. The study was carried out in the period of 2011-2013 on 18 food and beverages sample companies, which were selected from 20 population companies. Years of 2014 and 2015 are used to confirm the bankruptcy of companies with such potential predicted during 2011-2013. The model predicts that five out of 18 sample companies has the potential of bankruptcy; they are PT. Davomas Abadi, Tbk., PT. Tiga Pilar Sejahtera Food, Tbk., PT. Tunas Baru Lampung, Tbk., PT. Ultra Jaya Milk Industry, Tbk., and PT. Wilmar Cahaya Indonesia, Tbk. The validation of the model result does not find the predicted bankruptcy taking place during 2014 and 2015. It suggests that the model is not accurate in predicting bankruptcy on the research sample. Keywords: bankruptcy potential, Springate model, financial distress